The post-activation effect with two different conditioning stimuli on drop jump performance in pre-adolescent female gymnasts - Dallas, G.; Pappas, P.; Ntalla, C.; Paradisis, G. (Journal of Physical Education and Sport, 2018)
The purpose of this study was to examine the post-activation potentiation effects of two different conditioning stimuli (Rondat and double tuck jumps) on drop jump height, Contact time, and Power; and to determine whether strong gymnasts are able to elicit post activation potentiation earlier than weaker gymnasts during a drop jump test in pre-adolescent female gymnasts. Twenty-nine moderately trained female gymnasts, aged 9 to 13 years old (age = 11.75 ± 1.31 years, body weight = 40.40 ± 10.84 Kg, body height = 147.87 ± 11.22 cm,) volunteered to participate in this study. Each subject performed a drop jump before, immediately after and 3, 6, and 9 minutes after two different conditioning stimuli; the first consisted of 10 repetitions of Rondat exercise and the second consisted of 2 set x 5 repetitions of double tuck jumps. According to the results both conditioning stimuli revealed consistent tendency for greater jump heights during the drop jump condition. The applied conditioning stimuli were not adequate to produce post-activation potentiation effect due to their low volume. The researchers therefore suggested that both conditioning stimuli could be added to a warm-up prior to either training efforts or prior to competitions in order to increase explosive power and jumping ability in preadolescent female gymnasts. However, changes must reach a certain threshold considering the exercises intensity and volume in order to lead to a beneficial outcome even to preadolescent gymnasts.